Norm Transfer in US Technology Transfer: A Lesson for Policy Makers - Christopher Barton (Universidad Alberto Hurtado, 2021)
Social norms wield significant influence in public policy development. This paper offers a description of four norms that influence technology transfer within and between US institutions. These norms are located within the three environments of the US policy system: policy formation, policy implementation, and policy evaluation. Introducing the concept of ‘norm transfer’, we argue that norms cannot be assumed to permeate the entire policy system and that some prominent norms are in fact influential only in one or two of the policy environments. We demonstrate this idea using the case of technology transfer in the US, and suggest that understanding the role of norms in technology transfer is essential for improving the ability of universities and research labs to serve the public good. Our intention is to help policy makers better understand the influence of norms in the process of designing policy.